2024
DOI: 10.3390/jcm13061533
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Links between Physical Activity, Emotional Regulation, and Mental Well-Being in Jordanian University Students

Mohammad Al-Wardat,
Chiara Salimei,
Hassan Alrabbaie
et al.

Abstract: Background: University students face multiple stressors that negatively impact their mental well-being. Effective emotional regulation and physical activity are crucial for mood management and overall health. This study explored the connection between physical activity, emotional regulation, and mental health symptoms (depression, anxiety, and stress) in Jordanian university students. Methods: A cross-sectional online survey involved 416 students (146 male and 270 female) from Jordanian universities. The surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Secondly, we can choose to leave the dysfunctional environment for a short time to carry out other activities to achieve adjustment. For example, choosing physical activities such as sports that are independent of related events, studies have shown that physical activity has a positive impact on mental health and emotional regulation [10].…”
Section: Suggestionmentioning
confidence: 99%
“…Secondly, we can choose to leave the dysfunctional environment for a short time to carry out other activities to achieve adjustment. For example, choosing physical activities such as sports that are independent of related events, studies have shown that physical activity has a positive impact on mental health and emotional regulation [10].…”
Section: Suggestionmentioning
confidence: 99%